The Aggregate Potential Of The Scotian Shelf, Canada - Gordon B. J. Fader (International Marine Minerals Society, 1995)
A regional assessment of the aggregate potential of the Scotian Shelf is presently being funded through a Canada-Nova Scotia Cooperation Agreement on Mineral Development. This assessment includes testing of seabed materials for their suitability in a variety of concrete, asphalt and other specialized applications. The glacial and postglacial Holocene history of the Scotian Shelf has been favourable for the formation of large deposits of sand and gravel that have potential for use as marine aggregate resources. Large banks and inner shelf areas of the seabed consist of basal transgressive sand and gravel of the Sable Island Sand and Gravel Formation. These sediments accumulated during the late Wisconsinan postglacial transgression, through sorting of glacial materials that were originally deposited beneath marine terminating glaciers. Some sandy deposits occur as low-stand deltas on the inner shelf at 70 m water depth and were formed during the maxi- mum low sea level stand, in early postglacial time, at approximately 12 000 yBP. Modern sediment transport processes have contributed to the formation of areas of large sand bedforms, such as the Cape Split sand wave field and other isolated sand waves of the inner Bay of Fundy, and Eastern Shoal on Banquereau. Sandy sediments, found in many transverse channels in the nearshore, offer a potential for placer gold where proximal to adjacent onshore epithermal gold deposits. Lithothamnion covered gravel occurs as a thin lag overlying glacial sediments in much of the nearshore. Relict gravel beach ridges have been eroded and redistributed through sub-littoral processes after passage of the transgressing beach front. Multibeam bathymetry, sidescan sonograms and high-resolution seismic reflection profiles are the main survey tools. Ground truth consists of large volume seabed samples, vibrocores and photographs. A preliminary assessment of the aggregate potential indicates that very large volumes of suitable aggregate lie in the offshore of southeast Canada.